Численно-полевой анализ магнитного поля трехфазного асинхронного двигателя в статике и динамике - Милых, Владимир Иванович; Шилкова, Лариса Васильевна (НТУ "ХПИ", 2016)
Представлены принципы и результаты численно-полевого расчета координатных и временных функций величин, характеризующих магнитное поле в активной зоне трехфазного асинхронного двигателя в режиме нагрузки. На примере двигателя мощностью 15 кВт анализируются угловые функции магнитной индукции (МИ) в зазоре, в зубцово-пазовых структурах ротора и статора, в спинке сердечника статора, радиальные функции МИ и напряженности магнитного поля в пазах и зубцах ротора и статора, а также временные функции МИ в точках зазора и сердечника статора, в точках, связанных с вращающимся ротором.

Presentation of the principles and the results of numerical-field calculation of the coordinate and temporal functions of quantities characterizing the magnetic field in the core of a three-phase induction motor (TAD) on load condition. Calculations of magnetic fields are carried out with the finite elements method by FEMM program. Calculations are automated by controlling the operation of the program by means of the scripts created in Lua language. The coordinate functions are obtained by a disposable calculation in statics, the temporal functions - in dynamics by the multi-position calculations of the rotating magnetic fields within the full rotation of the rotor. The test calculations are conducted on a 15 kW TAD. The expanded set includes more functions besides the traditional consideration of the coordinate (angular) function of magnetic induction in the gap, namely, there are the coordinate functions of the magnetic induction and tension of the magnetic field in the slots and teeth of the rotor and stator, and also the temporal functions of the magnetic induction in points of the gap and core of the stator, in points associated with the rotating rotor. The updated formation principles of the TAD calculation model are presented based on the design data with the original formation of the current structure in the rotor slots, and the author's principles of the multi-position calculation of the rotating magnetic fields of TAD are presented in dynamics. The unique temporal functions of magnetic induction are got in a number of points of the TAD magnetic system. Numerical-field analysis of the coordinate functions of the magnetic induction and tension of the magnetic field in a number of areas and their temporal functions at specific points revealed aspects that were previously unavailable using classical methods of calculation of the TAD magnetic circuit. It has shown how rough were the assumptions made in calculation of a magnetic circuit of electrical machines with these methods. The results demonstrated that when they were taken in account a TAD design process had a verification reserves in part of determining its electromagnetic parameters and magnetic loss of power.
Numerical-field analysis of the magnetic field of a three-phase induction motor in statics and dynamics
Keywords: трехфазный асинхронный двигатель; режим нагрузки; магнитные поля; численные расчеты; магнитная индукция; напряженность магнитного поля; координатные функции; временные функции